2010
DOI: 10.1002/ijc.25401
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis‐focused cell‐based SELEX generates aptamers inhibiting cell migration and invasion

Abstract: Metastasis, the capacity of tumour cells to disseminate and grow at distant sites, is the main factor in cancer mortality. Compounds inhibiting migration and invasion of cancer cells are promising candidates for anticancer therapy strategies. We have generated nuclease-resistant RNA ligands (aptamers) recognizing highly metastatic cells with high affinity and specificity, and inhibiting their migratory and invasive potentials. Aptamers were generated by a cell-based subtractive SELEX technology using isogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
(48 reference statements)
1
27
0
Order By: Relevance
“…In summary, the results of the present study have demonstrated that the entire live cell-SELEX procedure was simple, but effective in generating cancer cell-specific aptamers, as previously reported (12)(13)(14)(15)(16)(17)(18)(19)(20). By using this method, we have identified a DNA aptamer termed cy-apt 20 with tenable binding affinity and stability to AGS cells.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In summary, the results of the present study have demonstrated that the entire live cell-SELEX procedure was simple, but effective in generating cancer cell-specific aptamers, as previously reported (12)(13)(14)(15)(16)(17)(18)(19)(20). By using this method, we have identified a DNA aptamer termed cy-apt 20 with tenable binding affinity and stability to AGS cells.…”
Section: Discussionsupporting
confidence: 76%
“…A large number of useful aptamers generated by this method are applied in the study of tumor biology, and even in the diagnosis and therapeutics of various types of cancer (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The encouraging results obtained with aptamers combined with their intrinsic properties and the versatility of the live cell-SELEX procedure have led to the application of this technical method in the development of gastric cancer-specific DNA aptamers.…”
Section: Discussionmentioning
confidence: 99%
“…This approach also favors isolation of aptamers that bind to the native folding and/or modification state (e.g., glycosylation, phosphorylation, etc.) of potential target molecules17, 48, 49, 50 over other selection approaches. These aptamers might be employed to identify novel cell surface markers (e.g., receptors), which subsequently become internalized into cells via the endosomal pathway, and to elucidate the mechanisms underlying CKD progression.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, aptamers are specific to the molecular signature of a tumor cell type. Such cell-based SELEX have been performed on several tumor cells, including breast cancer cells [141], colorectal cancer cells [142], small-cell lung cancer [143,144], non-small cell lung cancer [145], liver cancer cells [146], leukemia cells [147,148], gastric cancer cells [149], pancreatic ductal adenocarcinoma cells [150], prostate cancer cells [101], metastatic cells [151,152], and tumor initiating cells [153]. For example, J.N.…”
Section: Protein- and Cell-based Selex Processesmentioning
confidence: 99%